Reconstruction of Electron and Ion Distribution Functions in a Magnetotail Reconnection Diffusion Region. Issue 7 (21st July 2020) - Ng, Jonathan; Chen, Li‐Jen; Hakim, Ammar; Bhattacharjee, Amitava
Abstract: In the diffusion region of magnetotail reconnection, particle distributions are highly structured, exhibiting triangular shapes and multiple striations that deviate dramatically from the Maxwellian distribution. Fully kinetic simulations have been demonstrated to be capable of producing the essential structures of the observed distribution functions, yet are computationally not feasible for 3D global simulations. The fluid models used for large‐scale simulations, on the other hand, do not have the kinetic physics necessary for describing reconnection accurately. Our study aims to bridge fully kinetic and fluid simulations by quantifying the information required to capture the non‐Maxwellian features in the distributions underlying the closures used in the fluid code. We compare the results of fully kinetic simulations with observed electron velocity distributions in a magnetotail reconnection diffusion region and use the maximum entropy model to reconstruct electron and ion distributions using various numbers of moments obtained from the simulation. Our results indicate that using only local moments, the maximum entropy model can reproduce many of the features of the distributions: (1) the electron outflow distribution with a tilted triangular structure is reproduced with 21 or more moments in agreement with Ng et al. (2018, https://doi.org/10.1063/1.5041758 ) and (2) counterstreaming distributions can be captured with the 35‐moment model when the separation in velocity space between the populations is large. Plain Language Summary: Fluid modeling of plasmas in collisionless environments such as the magnetosphere is challenging because the approximation that collisions are important does not hold. It is important to understand the motion of individual particles as collisions do not bring them back to equilibrium, However, this is computationally intensive and cannot be used to model the Earth at the present time. We use a recent fluid model which is based on maximizing the entropy of an underlying distribution of particles and attempt to reconstruct particle distributions during reconnection in the Earth's magnetotail. We show that most features of the distribution function can be reproduced using an increasing number of fluid moments. Key Points: Particle distribution functions in a reconnection diffusion region are reconstructed using a maximum entropy closure Kinetic features such as electron anisotropy and acceleration are reproduced Inclusion of fourth‐order velocity moments allows the modeling of counterstreaming populations